An MRI Signal Receiving Method Based on Radio Frequency Direct Band-Pass Sampling with System Generator - LIU Ying; FAN Shu-fei; SONG Ming-hui; ZHANG Hao-wei (Chinese Journal of Magnetic Resonance, 2019)
In this paper, the use of software radio technology for signal reception in magnetic resonance imaging (MRI) was attempted. A radio frequency direct band-pass sampling method was proposed for signal reception in MRI. For this method, a digital demodulation algorithm was designed and implemented with System Generator, a design and development tool of digital signal processing (DSP) developed by the Xilinx company. At the same time, a digital down conversion (DDC) system was designed and tested to flexibly implement the DDC function. The validity of the proposed receiving method was confirmed by numerical simulations and experiments.